The dehesa system of southern Spain and Portugal as a natural ecosystem mimic - Joffre, R; Rambal, S; Ratte, J P (Agroforestry Systems, 1999)
The dehesas of the southwestern Iberian Peninsula are ‘man-made’ ecosystems characterised by a savannah-like physiognomy. The trees are viewed as an integrated part of the system, and as a result are planted, managed, and regularly pruned. Palynological and historical evidence of the manipulation of initial ecosystems by man to obtain a savannah-like ecosystem is presented. The ecological functions of the tree are detailed using results obtained at two complementary scales. At the local scale, strong soil structural differences and functional differences in water budget and patterns of water use are observed under and outside the tree canopy. Using the concept of ecosystem mimicry, the two coexistent components of dehesas can be compared to two distant stages of a secondary succession characterised by very different behaviours. At the regional scale, evidence of relationships between tree density and mean annual precipitation over more than 5000 km2 suggests that the structure of these man-made agroecosystems have adjusted over the long-term and correspond to an optimal functional equilibrium based on the hydrological equilibrium hypothesis. Finally, the future of dehesas in the face of contemporary exogenous threats of economic and global environmental origin is discussed. 1. Introduction
Keywords: hydrological equilibrium; Mediterranean climate; optimality; Quercus ilex; Quercus suber; water balance